Quantitative EEG analysis in typical absence seizures: unveiling spectral dynamics and entropy patterns - Guerrero-Aranda, Alioth; Ramírez-Ponce, Evelin; Ramos-Quezada, Oscar; Paredes, Omar; Guzmán-Quezada, Erick; Genel-Espinoza, Alejandra; Romo-Vazquez, Rebeca; Vélez-Pérez, Hugo (Frontiers in Human Neuroscience, 2023)
A typical absence seizure is a generalized epileptic event characterized by a sudden, brief alteration of consciousness that serves as a hallmark for various generalized epilepsy syndromes.Distinguishing between similar interictal and ictal electroencephalographic (EEG) epileptiform patterns poses a challenge. However, quantitative EEG, particularly spectral analysis focused on EEG rhythms, shows potential for differentiation. This study was designed to investigate discernible differences in EEG spectral dynamics and entropy patterns content during the preictal and postictal periods compared to the interictal state. We analyzed 20 EEG ictal patterns from 11 patients with confirmed typical absence seizures, and assessed recordings made during the preictal, postictal, and interictal intervals. Power spectral density (PSD) was used for the quantitative analysis that focused on the delta, theta, alpha, and beta bands. In addition, we measured EEG signal complexity regularity using approximate (ApEn) and multi-scale sample entropy (MSE). Findings demonstrate a significant increase in delta and theta power in the preictal 1 Guerrero-Aranda et al.